Дослідження методів та моделей ідентифікації операторів інформаційної системи з використанням візуальних та тепловізійних даних - Одейчук, О. М. (ХНУРЕ, 2024)
This work focuses on analyzing, researching, and developing an integrated solution for monitoring the work hours of information system operators using both visual and thermal imaging data for the identification of individuals’ faces. A novel approach has been developed, which automates the data collection process via web cameras (capturing both visual and thermal images) and integrates facial recognition systems, using a convolutional neural network for visual data and support vector machine techniques for thermal imaging data.
Keywords: тепловізійні дані; ідентифікація операторів інформаційної системи